Preparation method and application of photodynamic / photothermal synergistic antibacterial MOF-based packaging film
By combining polydopamine-coated porphyrin metal organic frame nanoparticles with gelatin-carboxymethylcellulose film-forming substrate, a photodynamic/photothermal synergistic enhanced antibacterial packaging film was prepared, which solved the problems of poor mechanical properties and lack of antibacterial functions of bio-based food packaging materials, and achieved efficient food preservation effect.
Patent Information
- Application Number
- CN202310354473.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-04-04
AI Technical Summary
The existing bio-based food packaging materials have poor mechanical properties, low moisture resistance, and lack antibacterial or antioxidant functions, which leads to food being easily corrupted and deteriorated during storage, limiting its large-scale industrial production.
The solution casting method was used to combine the polydopamine-coated porphyrin metal organic frame nanoparticles (PCN@PDA) with gelatin-carboxymethylcellulose (GC) film-forming substrate to prepare a photodynamic/photothermal synergistic enhanced antibacterial packaging film (PP/GC).
It significantly improves the mechanical properties, water barrier properties and ultraviolet barrier properties of the film, and has a killing effect of more than 99% on Staphylococcus aureus and E. coli within 15 minutes, delaying the spoilage and deterioration of cold fresh meat and prolonging the food shelf life of pork.
Smart Images

Figure CN116396512B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging films, and in particular to a preparation method and application of a photodynamic / photothermal synergistic antibacterial MOF-based packaging film. Background Art
[0002] At present, it has become a social consensus that fresh food, especially meat and meat products, are extremely easy to spoil. Compared with traditional methods such as drying, freezing, microwave and chemical impregnation, food packaging can not only prevent the deterioration of food nutrients and the growth of foodborne pathogens from the inside, but also block the harmful factors in the external environment (temperature, light, moisture, microorganisms, physical damage, etc.) from affecting food texture and safety. Therefore, it plays a vital role in food supply chain and quality control. In particular, biopolymers such as naturally extracted proteins, polysaccharides, and lipids have attracted much attention due to their good film-forming properties, wide sources, easy availability, non-toxicity, pollution-free, and degradable properties. Commonly, there are three major categories of plant materials (starch, cellulose, zein, carnauba wax), animal materials (gelatin, chitosan, whey protein, casein) and microbial materials (xanthan gum, dextran, pullulan). The bio-based films prepared by the above bio-based cast casting show great potential to replace petroleum-based plastic packaging to solve environmental pollution problems.
[0003] Many studies have shown that protein / polysaccharide based binary composites can give full play to the synergistic effect of film-forming substrates. However, biopolymer films have poor mechanical properties, low moisture resistance, and do not have the functional properties such as antibacterial or antioxidant required for active packaging, which leads to the gradual loss of food and commercial value due to oxidation and microbial contamination during storage, limiting large-scale industrial production. In order to broaden the application scenarios of bio-based films, improving film performance by adding functional film fillers has become a research hotspot in recent years. At the same time, porphyrin-MOFs (PCN-224) has attracted widespread attention from scholars at home and abroad due to its intrinsic photodynamic and photothermal effects. Some literature has reported its research results in the field of antibacterial, but most studies focus on the basic research of PCN-224 crystals and powders, which have problems such as easy aggregation, high brittleness, difficult processing, poor water solubility, and low recovery rate, which limits the commercial application of PCN-224 in packaging technology. Summary of the invention
[0004] In view of the shortcomings of existing bio-based food packaging, the present invention uses gelatin-carboxymethyl cellulose (GC) as a film-forming substrate and polydopamine-coated porphyrin metal organic framework nanoparticles (PCN@PDA) as a membrane filler. The solution casting method is combined with the bio-based film-forming substrate to improve the processing performance and surface properties of PCN-224, and a photodynamic / photothermal synergistically enhanced antibacterial packaging film (PP / GC) is prepared.
[0005] Technical solution:
[0006] The present invention provides a method for preparing a gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles, comprising the following steps:
[0007] (1) dispersing H2TCPP, zirconium oxychloride octahydrate and benzoic acid in an organic solvent, mixing, and heating for reaction; after the reaction is completed, centrifuging and collecting the solid to obtain PCN-224 nanoparticles;
[0008] (2) mixing the obtained PCN-224 nanoparticles, dopamine hydrochloride (DA·HCl) and a buffer, mixing well, and reacting in the dark to obtain composite nanoparticles PCN@PDA coated with polydopamine on the surface;
[0009] (3) Dissolve carboxymethyl cellulose and gelatin in water, add glycerol, mix well, and obtain a mixed solution; continue to add the obtained composite nanoparticles PCN@PDA coated with polydopamine to the mixed solution, mix well, and obtain a film-forming solution; pour the film-forming solution into a mold, dry, and peel off to obtain a gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles, which is recorded as PP / GC composite film.
[0010] In one embodiment of the present invention, in step (1), the mass ratio of H2TCPP to zirconium oxychloride octahydrate is 1:(2-5); specifically, 1:3 may be selected.
[0011] In one embodiment of the present invention, in step (1), the mass fraction of benzoic acid relative to H2TCPP is 2%-5%; specifically, 2.8% may be selected.
[0012] In one embodiment of the present invention, in step (1), the organic solvent is DMF.
[0013] In one embodiment of the present invention, in step (1), the concentration of H2TCPP relative to the organic solvent is 0.5-5 mg / mL; specifically, 1 mg / mL can be selected.
[0014] In one embodiment of the present invention, in step (1), the temperature of the heating reaction is 80-100°C; specifically, 90°C may be selected.
[0015] In one embodiment of the present invention, in step (1), the heating reaction time is 2-8 hours, and specifically 5 hours can be selected.
[0016] In one embodiment of the present invention, in step (2), the mass ratio of PCN-224 nanoparticles to dopamine hydrochloride (DA·HCl) is 25:(0.5-5); specifically, 25:1.5 and 25:2.5 may be selected.
[0017] In one embodiment of the present invention, in step (2), the buffer solution is a Tris-HCl solution with a concentration of 10 mM and a pH of 8.5.
[0018] In one embodiment of the present invention, in step (2), the temperature of the light-proof reaction is room temperature and the time is 10-15 hours.
[0019] In one embodiment of the present invention, in step (3), the mass ratio of carboxymethyl cellulose to gelatin is 1:1.
[0020] In one embodiment of the present invention, in step (3), the amount of water relative to the total mass of carboxymethyl cellulose and gelatin is 30-80 mL / g; specifically, 50 mL / g may be selected.
[0021] In one embodiment of the present invention, in step (3), the amount of glycerol used relative to the total mass of carboxymethyl cellulose and gelatin is 10%-20%; specifically, 15% may be selected.
[0022] In one embodiment of the present invention, in step (3), the amount of composite nanoparticles PCN@PDA coated with polydopamine relative to the total mass of carboxymethyl cellulose and gelatin is 1%-7%; specifically, 3% and 5% may be selected.
[0023] In one embodiment of the present invention, in step (3), the composite nanoparticles PCN@PDA coated with polydopamine on the surface are first prepared into an aqueous solution with a concentration of 50 mg / mL, and then added into the mixed solution.
[0024] The present invention provides a gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles based on the above method.
[0025] The present invention also provides application of the gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles in food packaging.
[0026] The present invention also provides application of the gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles in the field of food preservation and antibacterial.
[0027] In one embodiment of the present invention, by comparing the photodegradation performance of methyl orange and the photothermal performance of PCN-224 before and after coating with polydopamine, an optimal raw material input ratio of dopamine hydrochloride and PCN-224 is explored to obtain PCN@PDA composite nanoparticles with photodynamic / photothermal synergistic enhancement performance. The prepared PCN@PDA composite structure is characterized by TEM, XRD, FT-IR, UV-vis, potential and particle size analysis.
[0028] In one embodiment of the present invention, the PCN@PDA nanoparticles with the best performance obtained in the previous step are mixed and stirred with a film-forming solution in a certain proportion by a solution casting method (the mass ratio of PCN@PDA nanoparticles to bio-based polymer is 0%, 1%, 3%, 5% and 7%, respectively), to obtain a series of film-forming solutions with different nanoparticle contents. After ultrasonic removal of bubbles, the solution is poured onto a plastic plate and placed in a 60°C oven for drying for 4 hours to obtain a PP / GC composite film. The physical and chemical structure and packaging properties of the PP / GC film are analyzed by means of SEM, XRD, FT-IR, mechanical properties test, UV barrier test, colorimetry test, water vapor permeability (WVP) test, water contact angle (WCA) measurement, etc., to obtain a composite film with the best packaging performance for subsequent research.
[0029] In one embodiment of the present invention, the antibacterial activity of the film against Staphylococcus aureus and Escherichia coli was evaluated by colony counting method. In addition, pork tenderloin was selected as an actual sample, which was fully covered with PP / GC film and placed in a glass plate, exposed to 660nm laser source at regular intervals, and sensory evaluation was performed regularly during storage, and the pH value, TVB-N value, and total colony count of the meat sample were measured.
[0030] Beneficial effects:
[0031] (1) The modification strategy of the present invention of coating a layer of polydopamine (PDA) on the surface of porphyrin-metal organic framework (PCN-224) can effectively improve the light absorption capacity and water solubility of MOF materials, and improve the interfacial adhesion and biocompatibility between MOF and biofilm-forming substrates; (2) The addition of PCN@PDA nanoparticles gives gelatin-carboxymethyl cellulose (GC) film photodynamic and photothermal properties; (3) After doping with nanoparticles, the mechanical properties, water barrier properties and ultraviolet barrier properties of the film are greatly improved; (4) The synthesized photoresponsive film (PP / GC) has a killing effect of more than 99% on Staphylococcus aureus and Escherichia coli within 15 minutes, and the film significantly delays the spoilage of fresh meat and extends the food shelf life of pork. In general, this work is of great significance to the development of photodynamic / photothermal synergistic antibacterial packaging films. The prepared PCN@PDA nanoparticles can be used as a functional film filler to improve the physical and chemical properties of gelatin-carboxymethyl cellulose films. At the same time, this invention combines the photodynamic and photothermal synergistic antibacterial strategies based on MOF materials with bio-based polymers for the first time and applies them to the field of food packaging, effectively constructing a method to improve the storage quality of pork, which has good application prospects in food preservation and provides guidance for further research on photoactive films. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1Morphological characterization diagrams of PCN-224 NPs obtained in Example 1; (a, c) TEM images of PCN-224 NPs and (b, d) PCN@PDA NPs and (e, f) their corresponding particle size distribution histograms.
[0033] Figure 2 Zeta potential (a), UV-vis curve (b), FTIR (c) and XRD (d) characterization diagrams of the nanoparticles before and after PDA coating.
[0034] Figure 3 For PCN-224, PCN@PDA 0.5 、PCN@PDA 1.5 、PCN@PDA 2.5 and PCN@PDA 5.0 At 660nm (1W / cm 2 ) photodegradation efficiency of methyl orange under irradiation (a), degradation reaction kinetics (b), infrared thermal image (c) and photothermal temperature rise curve (d).
[0035] Figure 4 SEM surface and cross-sectional images of GC film and different PP / GC films.
[0036] Figure 5 UV-vis spectra (a), color difference analysis (b), FTIR (c) and XRD characterization (d) of GC film and different PP / GC films.
[0037] Figure 6 Mechanical properties (a), water vapor permeability (b) and water contact angle performance tests (c) of GC film and different PP / GC films.
[0038] Figure 7 Antibacterial activities of GC membrane and different PP / GC membranes against Staphylococcus aureus (a, b) and Escherichia coli (c, d).
[0039] Figure 8 Sensory evaluation (a), total bacterial count (b), pH value (c) and volatile basic total nitrogen (TVB-N value) (d) of GC membrane and different PP / GC membranes after 8-day preservation of pork. DETAILED DESCRIPTION
[0040] The test method involved in the present invention is:
[0041] Morphological and structural characterization of PP / GC composite films
[0042] The effects of different contents of PCN@PDANPs on the surface and cross-sectional morphology of the film were analyzed using a SU8100 scanning electron microscope (SEM). The film was cut into 15 mm × 15 mm in size, pasted on the surface of a conductive adhesive and placed on a sample stage. It was then gold-sprayed and observed at an accelerating voltage of 15 kV. The film samples were analyzed at 4000 cm using a Fourier transform infrared (FT-IR) spectrometer in attenuated total reflection (ATR) mode. -1 Up to 500cm -1 Chemical structure and functional group variations across the wavenumber range with a resolution of 2 cm -1 Each sample was scanned 32 times. X-ray diffractometer (XRD) was used to study the crystal structure of the film.
[0043] Surface color and optical properties of PP / GC composite films
[0044] Different films were covered on the colored school badge images and digital photos were taken to clearly reflect the appearance characteristics of the films. A 30mm×10mm film sample was attached to the outer wall of a cuvette, and the UV-vis absorption spectrum of the film in the wavelength range of 200-800nm was measured using an ultraviolet spectrophotometer with air as a reference. By calculating the film at 280nm (T 280 ) and 660nm(T 660 ) to evaluate the UV blocking performance and transparency of the film. At the same time, a colorimeter was used to measure the color change of the films doped with different contents of PCN@PDANPs, and the L * Value (brightness), a * Value (green / red) and b * The total color difference ΔE was calculated according to the following equation:
[0045]
[0046] Among them, ΔL, Δa and Δb represent the difference between the measured value of each sample and the standard white plate, respectively.
[0047] Thickness and mechanical properties of PP / GC composite films
[0048] The thickness of the film samples was measured using a flat-head digital thickness gauge (Shenzhen Huike Metrology and Testing Technology Co., Ltd.), with a probe diameter of 10 mm and an accuracy of 0.001 mm. Five different positions of each film were randomly selected for measurement. Referring to ASTM standard method D882-10, the tensile strength (TS) and elongation at break (EB) of the film were analyzed using a physical property tester (TA-XT plus). All film samples were cut into 50×10 mm rectangles, with the initial clamping distance set to 20 mm and the test speed set to 0.5 mm / s. Each sample group was measured three times and the results were calculated according to the following formula:
[0049]
[0050]
[0051] Here, F is the maximum stress (N), A is the cross-sectional area of the film (mm 2 ), L1 is the length of the film before breaking (mm), and L0 is the initial length of the film (mm).
[0052] Water vapor permeability (WVP) and water contact angle (WCA) of PP / GC composite films
[0053] The water vapor permeability (WVP) of the film is tested according to the E96-E95 ASTM standard method with slight modifications. The final result is calculated according to the following formula:
[0054]
[0055]
[0056] Here, WVTR is the water vapor transmission rate (g / m 2 ·s), W is the weight increased after absorbing water vapor (g), S is the exposed area of the film (m 2 ), t is the time interval (s), C is the film thickness (mm), and ΔP is the relative pressure difference on both sides of the film (kPa).
[0057] The surface wettability of the film was studied using an OCA15EC optical contact angle meter (De Fei Instrument Co., Ltd., Germany). A drop of 5 μL of water was dripped from a syringe onto the film surface, and the contact angle of the water droplet on the film surface at the interface of solid, liquid and gas was measured. Each sample was measured at least three times.
[0058] Test on the photodegradation performance of dyes in PP / GC composite films
[0059] At 660nm (1W / cm 2) laser irradiation was used to measure the MO photodegradation ability and corresponding photodegradation rate of the films. Briefly, equal weights of different films (25 mg) were placed in 10 mL of MO aqueous solution (10 mg / mL) and stirred in the dark for 30 min to reach desorption-adsorption equilibrium. The mixed solution was then irradiated with 660 nm light for different times (0, 10, 20, 30, 40 min), and the concentration of MO in the supernatant was monitored at 465 nm using a UV-1800 spectrophotometer. The MO degradation efficiency was calculated according to the following equation:
[0060]
[0061] C0 represents the initial concentration of MO solution, C t is the concentration of MO solution measured at reaction t min. In addition, the apparent rate constant k can be calculated by the pseudo-first-order kinetic equation as follows:
[0062]
[0063] Photothermal performance test of PP / GC composite film
[0064] At 660nm (1W / cm 2 ) The photothermal properties of the films were evaluated within 15 min of laser irradiation. The infrared thermal images and temperature changes of each film were obtained using a FOTRIC-225 infrared thermal imager.
[0065] Antibacterial performance test of PP / GC composite film
[0066] The antibacterial activity of the prepared film against Staphylococcus aureus and Escherichia coli was evaluated by plate colony counting method. 7 CFU / mL bacterial suspension: The activated Staphylococcus aureus and Escherichia coli were cultured in LB liquid culture at 37°C for 12 h, the obtained bacterial suspension was centrifuged (4500 rpm, 5 min), washed three times with 0.9% sterile saline, and adjusted to a concentration of about 10 7 CFU / mL (OD600 = 0.5). The same mass of different film samples (5 mg) were added to the EP tubes, followed by a certain volume of bacterial suspension (200 μL), and then irradiated with 660 nm (1 W / cm 2 ) Laser irradiation for 0min, 5min, 10min and 15min. 100μL of the bacterial suspension diluted to an appropriate multiple was spread on the LB plate and placed in a 37℃ incubator overnight. The number of bacterial colonies on each plate was counted the next day. The GC membrane without light was used as the control group, and the bacterial survival rate was calculated by the following formula:
[0067]
[0068] Here, N and N c They represent the colony counts (CFU / mL) of the experimental group and the control group, respectively; at the same time, the inhibition rate (%) can be obtained by subtracting the colony count (log CFU / mL) of the experimental group from the colony count (log CFU / mL) of the control group.
[0069] Application of PP / GC composite film in pork preservation
[0070] The pork used in this study was the longissimus dorsi muscle of Erhualian pigs 8-12 hours after death, purchased from T&T Supermarket in Wuxi, Jiangsu Province. 500 g of pork was purchased each time, packed in ice boxes and transported back to the laboratory. The excess fat and fascia on the surface were removed, and the pork was cut into small pieces of 3 cm × 3 cm × 2 cm and placed in a glass dish. The meat samples were fully coated with GC film without PCN@PDANPs added (as the control group) and 5% PP / GC film (as the experimental group), respectively. The blank group was the sample without film coating on the surface and directly exposed to the air. All meat samples were stored in a refrigerator at 4°C. Among them, the samples in the experimental group were treated with light (660nm light source for 15 minutes) on the 1st, 3rd and 5th days, and the color, smell, viscosity, elasticity and overall acceptability of the meat samples were sensory evaluated on the 0th, 2nd, 4th, 6th and 8th days, respectively. The evaluation was conducted by a 10-person team and the team members were trained according to GB / T 9959.1-2019 Fresh and Frozen Pork and Pork By-products. In addition, the physical and chemical indicators that can reflect the freshness of cold fresh meat, such as pH value, TVB-N value, and total colony count, were measured, and each sample was repeated three times in parallel.
[0071] Example 1
[0072] Synthesis of polydopamine-coated PCN-224 nanoparticles:
[0073] PCN-224 nanoparticles were synthesized by solvothermal method: 100 mL of N,N-dimethylformamide (DMF) solution containing 100 mg H2TCPP, 300 mg zirconium oxychloride octahydrate and 2.8 g benzoic acid was added to a 250 mL round-bottom flask; after ultrasonic treatment for 15 min, it was placed in a 90 °C oil bath and heated for 5 h; then the product was collected by centrifugation (11000 rpm, 20 min) and washed 3 times with DMF, and PCN-224 nanoparticles were obtained after drying.
[0074] Preparation of polydopamine-coated PCN@PDA composite nanoparticles: Based on the fact that dopamine hydrochloride (DA·HCl) can undergo oxidative self-polymerization under alkaline conditions and adhere to the surface of a solid matrix, 25 mg of the prepared PCN-224 nanoparticles were mixed with 1.5 mg of dopamine hydrochloride and added to 5 mL of Tris-HCl solution (10 mM, pH = 8.5). After ultrasonication for 10 min, the solution was placed at room temperature and protected from light and stirred continuously for 12 h. Finally, composite nanoparticles PCN@PDA with polydopamine content were obtained by centrifugal washing, placed in a vacuum drying oven at 60°C overnight, ground into powder and stored in the dark for later use.
[0075] According to the above process, the dosage of dopamine hydrochloride was replaced by 0.5 mg, 2.5 mg and 5.0 mg respectively, and the other contents remained unchanged to obtain the corresponding composite nanoparticles with polydopamine content, which were recorded as PCN@PDA 0.5 、PCN@PDA 2.5 、PCN@PDA 5.0 .
[0076] Preparation of gelatin-carboxymethyl cellulose composite membrane doped with PCN@PDA nanoparticles:
[0077] 0.5 g of carboxymethyl cellulose and 0.5 g of gelatin were dissolved in 50 mL of deionized water, respectively, and stirred vigorously at 60 ° C for 30 min. The two were mixed and 15 wt% of glycerol was added to the total mass of carboxymethyl cellulose and gelatin, and heated and stirred at 90 ° C for 1 hour to obtain a mixed solution; then, 5 wt% of the weight of carboxymethyl cellulose and gelatin PCN@PDA nanoparticles (PCN@PDA nanoparticles were configured into a 50 mg / mL concentration of aqueous solution and added to the mixed solution) were added, and after stirring for 30 min, the film-forming solution was quickly poured into a plastic plate with a diameter of 10 cm and placed in a 60 ° C oven for 4 hours; the dried film was peeled off from the plate and equilibrated at room temperature with a humidity of 50±1% RH for 48 hours to obtain a gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles, recorded as PP / GC composite film (or 5% PP / GC).
[0078] As a comparison, gelatin-carboxymethyl cellulose film without adding PCN@PDA was prepared by the same method and recorded as GC film.
[0079] Example 2
[0080] Synthesis of polydopamine-coated PCN-224 nanoparticles: Same as Example 1.
[0081] Preparation of gelatin-carboxymethyl cellulose composite membrane doped with PCN@PDA nanoparticles: Referring to Example 1, only the addition amount of PCN@PDA nanoparticles was changed to 1wt%, 3wt%, and 7wt%, respectively, and the other factors remained unchanged, to obtain the corresponding 1% PP / GC, 3% PP / GC, and 7% PP / GC composite membranes.
[0082] Characterize the structure of the PP / GC composite film obtained above and test its packaging performance, photodegradation dye performance, and photothermal performance:
[0083] Scanning electron microscopy was used to analyze the film morphology, Fourier transform infrared spectrometer (ATR) mode was used to analyze the chemical structure and functional group changes of the film samples, and X-ray diffractometer was used to record the crystal structure of the film samples. The above characterizations can prove that PCN@PDA in the embodiment is successfully doped into the GC film and has good biocompatibility.
[0084] The tensile strength (TS) and elongation at break (EB) of the film were measured by a texture analyzer, and the water vapor permeability (WVP) and water contact angle (WCA) of the film were also measured. The results show that the PP / GC film doped with 5%wt in Example 1 has the best mechanical strength, the strongest water barrier, and a strong UV barrier. The details are shown in Table 1-2.
[0085] Table 1 Mechanical properties, water vapor transmission rate (WVP) and water contact angle (WCA) results of different PP / GC composite films
[0086]
[0087] In addition, the UV-visible absorption spectrum of the film in the wavelength range of 200-800nm was measured, and the UV barrier and transparency of the film were evaluated by calculating the transmittance of the film at 280nm and 660nm. The color change of the film was measured using a colorimeter, and the L*, a*, b* values and total color difference of each sample were recorded. The data are shown in Table 2.
[0088] The UV blocking ability helps to protect food from light damage, while the appropriate transparency allows us to visually identify the specific condition of the food inside the package, both of which are of great significance in food packaging. After adding 1%wt, 3%wt, 5%wt and 7%wt PCN@PDANPs, the GC film 280The transmittance at 660nm decreased from 52.24% to 28.12%, 14.72%, 8.71% and 5.68% respectively. These results show that PPNPs can improve the UV blocking performance of the composite film in a dose-dependent manner. At the same time, the addition of PPNPs slightly reduced the transmittance of the film at 660nm, indicating that the transparency of the film has been lost to a certain extent, but the clear school logo pattern (such as Figure 4 shown).
[0089] In addition, with the increase of the doping amount of nanoparticles, the appearance color of the film gradually deepened from colorless to dark brown, showing the color of PCN@PDA NPs themselves.
[0090] Table 2 Chromaticity analysis of pure GC film and different PP / GC films and transmittance at 280nm and 660nm wavelengths
[0091]
[0092] Note: Different lowercase letters (ae) in the same column indicate significant differences (p<0.05).
[0093] According to the analysis in Table 2, there are significant differences in L* and ΔE values among all films (P<0.05). As the PPNPs content increases, the color of the film gradually darkens and the brightness decreases sharply. Given that consumers' sensory evaluation of food packaging materials affects their desire to buy, it is necessary to control the packaging color to maintain an acceptable appearance. From this perspective, 3% and 5% PP / GC films may be more suitable for practical applications.
[0094] In order to evaluate the photodegradation of methyl orange by different PP / GC films, 25 mg of PP / GC composite film was placed in 10 mL of methyl orange (MO) solution and stirred in the dark for 30 minutes; then, the mixed solution was exposed to 660 nm light at different time intervals, and the concentration of MO in the supernatant was measured at 465 nm using a UV-visible spectrophotometer and the degradation efficiency was calculated. At the same time, the relevant kinetic analysis of this photodegradation process was performed. The experiment showed that the photodegradation ability of the PP / GC composite film showed PCN@PDA concentration dependence and light exposure time dependence. The specific results are as follows:
[0095] Table 3 Photodegradation ability of PCN@PDA nanoparticles (fixed illumination for 40 min)
[0096]
[0097] Table 4 Photodegradation ability of PP / GC composite film (fixed 5% doping amount)
[0098] Lighting time 0min 10min 20min 30min 40min Photodegradation ability 0% 18.5% 46.9% 57.4% 64.9%
[0099] Finally, in the photothermal performance test, the film was exposed to a 660nm laser (1W / cm 2 ) for 15 minutes, and the infrared thermal image of the film was captured by an infrared thermal imager and the film temperature rise curve was fitted. The results show that with the increase of PCN@PDA content in the film, the heating rate and photothermal conversion capacity are also rapidly increasing. After 60 seconds of illumination, the temperature rises to a stable platform and can maintain the highest temperature unchanged, which indicates that the heat in the film can quickly reach equilibrium without loss.
[0100] Example 3
[0101] Effects of different polydopamine contents on photodegradable dye performance and photothermal properties:
[0102] Preparation of PCN@PDA composite nanoparticles with different polydopamine coating amounts: 25 mg of the PCN-224 nanoparticles prepared in Example 1 were mixed with 0.5 mg, 1.5 mg, 2.5 mg and 5.0 mg of dopamine hydrochloride, respectively, and added to 5 mL of Tris-HCl solution (10 mM, pH = 8.5). After ultrasonication for 10 min, the solution was placed at room temperature and protected from light and stirred continuously for 12 h; finally, composite nanoparticles PCN@PDA with different polydopamine contents were obtained by centrifugation and washing. 0.5 、PCN@PDA 2.5 、PCN@PDA 5.0 , placed in a 60°C vacuum drying oven overnight, ground into powder and stored away from light for later use.
[0103] Prepare 10 mL of methyl orange solution with an initial concentration of 10 mg / mL in a small glass bottle, and add 1.5 mg of PCN-224 and PCN@PDA granular powders with different polydopamine contents (PCN@PDA 0.5 、PCN@PDA 1.5 、PCN@PDA 2.5 、PCN@PDA 5.0 ), after being dispersed uniformly by ultrasound for 10 min, the mixture was stirred for 30 min in a dark environment to reach desorption-adsorption equilibrium, and then the mixture was heated at 660 nm (1 W / cm 2 ) light source for 40 min, during which 1 mL of solution was drawn every 10 min, and the absorbance value of the supernatant at 465 nm was measured by ultraviolet spectrophotometer after centrifugation. PCN-224NPs of equal mass were set as the control group. The MO degradation efficiency was calculated according to the following equation:
[0104]
[0105] C0 represents the initial concentration of MO solution, C tis the concentration of MO solution measured at reaction t min. In addition, the apparent rate constant k can be calculated by the pseudo-first-order kinetic equation as follows:
[0106] The results showed that compared with pure PCN-224, PCN@PDA 0.5 and PCN@PDA 1.5 It showed better photodegradation dye performance, which proved that the coating of PDA enhanced the absorption capacity of MOF materials to visible light and had excellent charge transfer ability, which could effectively avoid the electron-hole recombination of photocatalysts. 2.5 and PCN@PDA 5.0 The degradation efficiency is significantly lower than that of PCN@PDA 1.5 , it is inferred that there is an optimum PDA content to achieve the best photodegradation performance, because an excessively thick PDA layer hinders the ability of PCN-224 to capture light, resulting in a decrease in the photocatalytic efficiency.
[0107] 200 μL of a series of PCN@PDA aqueous solutions (PCN@PDA) with a concentration of 300 μg / mL were added. 0.5 、PCN@PDA 1.5 、PCN@PDA 2.5 and PCN@PDA 5.0 The solution was placed in a 96-well plate and irradiated with 660 nm light for 15 min. The temperature change of the solution was monitored in real time by a FOTRIC-225 infrared thermal imager (Shanghai Feichu Technology Co., Ltd.) and infrared thermal images were taken at 0s, 30s, 60s, 120s and 300s of illumination. The data were automatically collected using FOTRIC AnalyzIR professional analysis software to draw the temperature rise curve of each sample and characterize its photothermal conversion characteristics / photothermal heating performance.
[0108] The results show that after 15 min of irradiation, the temperature of pure PCN-224 increased from 26.7°C to 36.5°C. 0.5 、PCN@PDA 1.5 、PCN@PDA 2.5 and PCN@PDA 5.0 The highest temperatures reached 51.3°C, 57.6°C, 63.2°C and 73.9°C, respectively, and then reached a stable platform temperature. It can be seen that the prepared composite material has a good photothermal effect, and the temperature rise can be controlled by adjusting the content of PDA. Real-time photothermal images confirmed that the prepared PCN@PDA nanoparticles can effectively absorb 660nm light and convert it into heat energy.
[0109] Example 4
[0110] Antimicrobial activity test of PP / GC composite film and its application in pork preservation:
[0111] The antibacterial activity of the film against Staphylococcus aureus and Escherichia coli was evaluated by colony counting method. Different film pieces of equal mass were added to EP tubes respectively. Then, a certain volume of bacterial suspension was dropped onto the film and exposed to 660nm laser for 0min and 15min respectively. 100μL of the diluted bacterial suspension was spread on the LB plate and cultured at 37℃ overnight, and the number of colonies on each plate was counted. Under 660nm irradiation, the GC film did not show antibacterial effect. The film with PCN@PDA added had an inhibitory effect on the growth of bacteria, and the bacterial survival rate decreased with the increase of illumination time. At the same time, the antibacterial effect of PP / GC film increased with the increase of PCN@PDA content. The antibacterial rates of 7% PP / GC film against Staphylococcus aureus and Escherichia coli were 99.9% and 99.5% respectively after irradiation for 15min.
[0112] Table 5 Antibacterial activity of different PP / GC composite films
[0113] PP / GC composite film Staphylococcus aureus inhibition rate Escherichia coli inhibition rate Example 1 (5%) 99.5% 97.9% Example 2 (1%) 29.6% 13.3% Example 2 (3%) 68.3% 54.0% Example 2 (7%) 99.9% 99.5%
[0114] In addition, pork tenderloin was selected as an actual sample, cut into small pieces and placed in a glass dish, and the meat pieces were fully coated with the PP / GC film obtained in Example 1, and were subjected to light treatment (660 nm laser source irradiation for 10 min) on the 1st, 3rd, and 5th days, respectively. During the storage process, the meat samples were subjected to sensory evaluation on the 0th, 2nd, 4th, 6th, and 8th days, and the pH value, TVB-N value, and total bacterial count of the meat samples were measured.
[0115] The experimental results show that PP / GC film has a certain inhibitory effect on the growth of microorganisms in meat, thereby reducing the production of volatile basic ammonia and inhibiting the increase in pH value. After the sixth day of refrigeration, the total colony count is still within the standard of sub-fresh meat, and the shelf life is extended to 6-8 days.
[0116] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles, characterized in that: The steps include: (1) Dispersing H2TCPP, zirconium oxychloride octahydrate and benzoic acid in an organic solvent, mixing and heating for reaction; after the reaction is completed, centrifuging and collecting the solid to obtain PCN-224 nanoparticles; the mass ratio of H2TCPP to zirconium oxychloride octahydrate is 1:2-5; the mass fraction of benzoic acid relative to H2TCPP is 2%-5%; the concentration of H2TCPP relative to the organic solvent is 0.5-5 mg / mL; (2) Mix the obtained PCN-224 nanoparticles, dopamine hydrochloride and buffer, mix well, and react in the dark to obtain composite nanoparticles PCN@PDA coated with polydopamine on the surface; the mass ratio of PCN-224 nanoparticles to dopamine hydrochloride is 25:0.5-5; (3) Dissolve carboxymethyl cellulose and gelatin in water, add glycerol, mix well to obtain a mixed solution; continue to add the obtained composite nanoparticles PCN@PDA coated with polydopamine to the mixed solution, mix well to obtain a film-forming solution; pour the film-forming solution into a mold, dry, and peel off to obtain a gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles, recorded as PP / GC composite film; the amount of composite nanoparticles PCN@PDA coated with polydopamine relative to the total mass of carboxymethyl cellulose and gelatin is 1%-7%; the amount of glycerol relative to the total mass of carboxymethyl cellulose and gelatin is 10%-20%; the mass ratio of carboxymethyl cellulose to gelatin is 1:
1.
2. A gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles prepared by the method of claim 1.
3. Use of the gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles as claimed in claim 2 in food packaging.
4. Application of the gelatin-carboxymethyl cellulose composite film doped with PCN@PDA nanoparticles as claimed in claim 2 in the field of food preservation and antibacterial.
Citation Information
Patent Citations
Molded metal-organic framework material and molding method thereof
CN107029670A
Polydopamine-coated zirconium-based metal organic material as well as preparation method and application thereof
CN112442185A